2018
DOI: 10.1038/s41418-018-0173-9
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and necroinflammation, a yet poorly explored link

Abstract: Ferroptosis is a non-apoptotic form of cell death characterized by overwhelming iron-dependent lipid peroxidation, which contributes to a number of pathologies, most notably tissue ischemia/reperfusion injury, neurodegeneration and cancer. Cysteine availability, glutathione biosynthesis, polyunsaturated fatty acid metabolism and modulation of the phospholipidome are the key events of this necrotic cell death pathway. Non-enzymatic and enzymatic lipoxygenase (LOX)-mediated lipid peroxidation of lipid bilayers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
203
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(217 citation statements)
references
References 90 publications
3
203
0
Order By: Relevance
“…Indeed, we observed that I/R upregulated the expression of inflammatory cytokines in the liver, which was prevented by Fer‐1, suggesting that ferroptosis‐mediated cell death is an upstream event for inflammatory responses during hepatic I/R injury. Recently, inflammation induced by cell death in a necrotic manner has been referred to as “necroinflammation.” In particular, ferroptosis‐induced necroinflammation has received considerable attention . In this scenario, hepatic I/R causes hepatocyte ferroptosis and triggers extracellular release of cellular contents known as damage‐associated molecular patterns, which are in turn recognized by pattern recognition receptors including Toll‐like receptors or Nod‐like receptors on Kupffer cells and endothelial cells, and eventually induce inflammatory responses and enhance liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we observed that I/R upregulated the expression of inflammatory cytokines in the liver, which was prevented by Fer‐1, suggesting that ferroptosis‐mediated cell death is an upstream event for inflammatory responses during hepatic I/R injury. Recently, inflammation induced by cell death in a necrotic manner has been referred to as “necroinflammation.” In particular, ferroptosis‐induced necroinflammation has received considerable attention . In this scenario, hepatic I/R causes hepatocyte ferroptosis and triggers extracellular release of cellular contents known as damage‐associated molecular patterns, which are in turn recognized by pattern recognition receptors including Toll‐like receptors or Nod‐like receptors on Kupffer cells and endothelial cells, and eventually induce inflammatory responses and enhance liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other types of regulated necrosis such as necroptosis and pyroptosis, ferroptosis leads to complete plasma membrane disruption and the final bursting of the cell (Dixon et al, 2012, Proneth & Conrad, 2019. Increase in cytosolic Ca 2+ , cell swelling, rounding, as well as plasma membrane breakdown have been described as hallmarks for necroptosis and pyroptosis, which represent critical differences to apoptosis (Frank & Vince, 2018, Ros et al, 2017, Vandenabeele, Galluzzi et al, 2010.…”
Section: Sustained Increase In Cytosolic Ca 2+ Is a Hallmark Of Ferromentioning
confidence: 97%
“…Ferroptosis is a caspase-independent form of regulated cell death characterized by the generation of lethal amounts of iron-dependent lipid hydroperoxides in cellular membranes (Dixon, Lemberg et al, 2012. Cells dying via ferroptosis are characterized by plasma membrane rupture and release of otherwise confined intracellular components including pro-inflammatory damage-associated molecular patterns (DAMPs) (Proneth & Conrad, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is a mode of programmed cell death that is characterized by an iron-dependent accumulation of lipid peroxides [48]. Interestingly, ferroptosis is considered to be pro-inflammatory and immunogenic, due to release of damage-associated molecular patterns (DAMPs) [67,68]. Hence, besides the direct effects on the tumor cells, artesunate may also support anti-tumor immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, besides the direct effects on the tumor cells, artesunate may also support anti-tumor immune responses. However, direct evidence for this possibility is still scarce and further investigations on this topic are necessary [67]. Notwithstanding, following preclinical evaluation of the anti-tumoral activity of artesunate in recent years, we have now reached a phase of human trials for the treatment of cancer patients with artesunate.…”
Section: Discussionmentioning
confidence: 99%